MOLECULAR MECHANIZMS OF DEVELOPMENT OF INFLAMMATORY REACTIONS IN BURNS (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
In burns, interleukin-6 is released, triggering the production of acute-phase proteins in the liver. Hypermetabolism ensues, and at the same time muscle tissue is rapidly broken down. In burn victims, serum IL-6 levels peak approximately one week after the burn, and this increase coincides with an increase in endotoxin levels. Very high plasma levels are observed in dying patients. IL-6 stimulates antibody production (T-cell factor or factor released by T-lymphocytes). It promotes the maturation of B cells into antibody-producing plasma cells.